Characterization and classification of soils of the Rivers State University Teaching and Research Farm, Port Harcourt, Southern Nigeria - Kaananwii Dum Peter; Lucky Agbogun (Jurnal Ilmu Pertanian, 2022)
This study was conducted to characterize and classify the soils of the Teaching and Research Farm, Rivers State University, Port Harcourt, covering 30 hectares of land area. A rigid grid soil survey method at a very detailed level (100 × 100) m² (1 ha) with two mapping units identified and delineated. Each of the mapping unit was represented by a soil profile described from the lowest end to the upper part of the profiles to avoid contamination. Soil samples were collected for laboratory analysis from the various horizons identified. The results obtained, indicated that the soils were of Inceptisols/ Cambisol order, Udepts at the suborder level, Eutrudepts Great group level and Typic Eutrudepts (subgroup level). Thus, the drainage, parent materials, climate (rainfall), and vegetation of the area along with the geologic material, formed from the sedimentary rocks that were weathered into coastal plain sands and buried under alluvium at various degrees at different locations in the study area, greatly affected the soils of Teaching and Research Farm, Rivers State University, Port Harcourt, which are primarily Inceptisols/ Cambisols.